Behavioural and molecular study of methamphetamine use and addiction in a rat model /Sim Maw Shin - Sim , Maw Shin (2017)
Methamphetamine (METH) is a highly addictive psycho-stimulant that induces behavioral changes, most likely due to high level of METH-induced dopamine in the brain. Nucleus accumbens (NAc) and hippocampus are the critical part of the brain in which the changes occur in drug addiction. However, little is known about the underlying molecular mechanisms of METH-induced addiction on miRNA, transcriptome and protein expression. The main objectives of this study are to study the behavioral changes that occur with use and addiction to METH and to determine the global miRNA, transcriptome and protein profiling in the NAc and hippocampus of METH-addicted rats, and also to identify miRNAs, genes and proteins which are associated with METH exposure and addiction. The experimental rats were divided into 3 groups of 6 each: a control group, a single dose METH (5 mg/kg, i.p.) treatment group and a continuous 15 alternate days METH (0.25, 0.5, 1, 2, 3, 4, 5 mg/kg) treatment group. Addiction behavior in rats was determined using Conditioned Place Preference (CPP) task. The analysis of the miRNA and transcriptome profiling in the NAc and hippocampus was performed using Affymetric microarray GeneChip® System, while the protein profiling was performed using Thermo Scientific LTQ Orbitrap mass spectrometer. The results of the study showed that the continuous 15 alternate days METH treatment rats showed a preference for the drug-paired compartment of the CPP. However, a one-time acute treatment with 5 mg/kg METH did not show any significant difference in preference when compared with the control group. Addiction behavior was only seen when rats consumed increasing doses of METH over a continuous exposure period. We also found that the continuous exposure with administration of increasing doses may reduce the learning and memory ability in rats. Differential molecular profiling indicated that 170 miRNAs, 3 genes and 15 proteins were up-regulated, while iv 4 miRNAs, 26 genes and 27 proteins were down-regulated in the NAc when the continuous METH treatment group was compared with the controls. In comparing the METH addiction group (continuous treatment) with the non-addiction group (acute treatment), 38 miRNAs, 6 genes and 25 proteins were shown to be up-regulated and 4 miRNAs, 32 genes and 15 proteins were down-regulated. In the hippocampus, 180 miRNAs, 8 genes and 28 proteins were up-regulated, while 10 miRNAs, 13 genes and 5 proteins were down-regulated when the continuous treatment group was compared with the controls. In comparing the addiction group with those without addiction, 104 miRNAs, 10 genes and 33 proteins were shown to be up-regulated and 5 miRNAs, 20 genes and 20 proteins were down-regulated. The level of significance applied was when changes were more than two fold change and with ANOVA and FDR test with p<0.05. Our results suggest that the rat model that has been developed is adequate as an addiction behavior model for METH, and that dynamic changes occur in the expression of mRNAs, miRNAs and proteins with METH exposure and addiction.